Learning English at Elementary School Level Using Computer Base Intraction (CBI) Method - Marjono Sugiono (Cattleya Darmaya Fortuna, 2022)
This study describes the collaboration of technological developments with learning systems in elementary schools with the sophistication of technology, it is easier for teachers to deliver learning materials to students without face to face. Authors get is that in the process of making a new system, it can be seen that to compile good information, the steps that need to be taken are to study the existing system, then design a system that can solve the problem, and finally implement the designed system.